Lifestyle Adaptations in Cardiometabolic Patients After Covid-19; [Adaptações No Estilo de Vida de Pacientes Cardiometabólicos Pós-Covid-19]; [Adaptaciones en el Estilo de Vida de Los Pacientes Cardiometabólicos Post-Covid-19] - De Sousa-Paiva, S (Universidad de Santander, 2024)
Introduction: Numerous factors contribute over time to changes in lifestyle behaviors, and the COVID-19 pandemic not only altered individuals routines but also influenced the factors affecting their chronic conditions. Objective: To understand the perception of patients with cardiometabolic diseases regarding adaptations to their lifestyle after contracting COVID-19. Materials and methods: This exploratory study with a qualitative approach was conducted with nine patients diagnosed with cardiometabolic diseases who tested positive for COVID-19. Data collection involved semi-structured audio-recorded interviews, which were transcribed and processed using IRAMUTEQ software. Results: The collective discourse revealed that mass contamination by the coronavirus and subsequent Long COVID triggered significant fears and anxieties, as well as increases in muscle pain, fatigue, and difficulties in maintaining blood pressure and/or glycemic control. These issues directly impacted the daily routines of infected patients. However, there was also an awakening due to changes in lifestyle. Discussion: The complexity of the experiences reported by infected patients influenced their desire to adopt a healthy lifestyle and seek knowledge. Conclusion: The number of patients affected by COVID-19 in its acute and long phases is concerning for both society and health professionals, highlighting the need to expand strategies aimed at quality care and ensuring adequate monitoring across different spheres of care. © 2024 Universidad de Santander. All rights reserved.